Based on "Chen-style Taijiquan Illustration" to explore the causes of knee pain in traditional Chen-style Taijiquan training (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Research purposes: It has great significance and value to conduct in-depth research on the causes of knee pain in the learning and training of traditional Chen-style Taijiquan, and it has a profound impact on the development of Taijiquan. According to existing research results, knee pain or injury is common during the learning and training of traditional Chen-style Taijiquan routines. Although Taijiquan, as one of the outstanding representatives of Chinese traditional martial arts, integrates the cultural essence of the Chinese nation, and there are a large amount of data and research analysis showing that Taijiquan has many benefits for the human body, however, it is undeniable fact that practicing and learning Chen-style Taijiquan may occur knee pain or injury. By reading the literature, it can be found that various studies analyzing the aspects of mechanics and medicine put forward certain suggestions and solutions for knee joint pain and injury, but they did not find specific reasons from Taijiquan Principles and Tai Chi Boxing Methods. Therefore, we try to base on "Chen-style Taijiquan Illustration" to find out the causes of knee pain and provide suggestions and solutions. Research methods: This article will mainly rely on the publication "Chen-Style Taijiquan Illustration" written by Chen Xin, the eighth-generation successor of Chen-Style Taijiquan in the Republic of China, and use the literature method to conduct research on related books, documents, and historical materials of Chen-Style Taijiquan. Targeting collection of literature in HowNet, collecting information on people with knee pain during Taijiquan practice, laying a reliable data reference foundation for subsequent research, and using logical analysis to analyze and summarize the information behind the data. In addition, We through our own teaching and practical experience, in-depth understanding of the specific situation of knee pain in Tai Chi training, and then actively explore and study potential factors, verify and enrich the cognition of knee pain formation. We believe that the detailed understanding will provide more specific and effective guidance for developing personalized teaching programs and strategies and provide help for avoiding knee pain promoting the health, safety, and effectiveness of Tai Chi training. Research results: through the collection of literature and data summary. In the relevant data, it can be found that the probability of knee pain during traditional Chen-style Taijiquan training is relatively high. Some literature shows that 175 people experience knee joint pain during the practice of Taijiquan, accounting for 49.30%, and the knee joints of both legs position no matter in the front, inside, and outside have different degrees of pain appear mainly dull pain. However, previous studies show that Tai Chi training can increase exercise capacity, improve knee motor function, and have a certain therapeutic effect on knee osteoarthritis. Therefore, it can be inferred that the occurrence of knee joint pain may be due to sports injuries caused by irregular technical movements during training. This article tries to analyze the training process in conjunction with "Chen-Style Taijiquan Illustrations". Because Chen-style Taijiquan emphasizes the whole body, just as in the boxing scriptures ", and when staying still everything stays still" the whole body remains in harmony. Therefore, slight errors in movements during Taijiquan training can cause problems with the movement as a whole, affecting the line of motion and stability of the knee. The technical movements of Taijiquan are different from other sports. The movements are ever-changing but inseparable from it. The core and power chain requirements of each move and style are the same when you understand and find every movement. During exercise, stillness is yin, and movement is yang. Therefore, the causes of knee joint pain can be found separately in each movement and stillness. stillness usually appears in the basic skills of Taijiquan or in the fixed form of each move. In the fixed form of Taijiquan, it is usually strictly required: Xuling Dingjin (the Baihui point on the top of the head is upward, the lower jaw is slightly retracted, and the eyes look forward.), Xuling Dingjin can make the shoulders relax and the upper body stand upright, so as to prevent the occurrence of bad postures such as hunchback and head forward. Loosening the waist and dropping the hips(The waist and hips are relaxing at the same time, and the pelvis is slightly rolling forward. In Taijiquan, it is called tightening the buttocks, but at the same time, the groin must not have the force to push outward, the caudal vertebrae downwards at this time.)and the back will naturally reach an upright state at this time. When the combination of Xuling ding jin and loose waist and hips meet the technical standards, this state is called standing upright in Taijiquan, with the body unbiased and the center of gravity vertically downward. Rounding crotch and bent knees (while loosening the waist and dropping the hips, hold the two hips open, the knees relax with the hips and bend slightly and buckle inward slightly so that the front of the knees are aligned with the toes). In actual movement, it can be observed that if one of these requirements is not implemented correctly, then the others are likely to be problematic as well. such as Xuling ding jin does not meet the standard, the person as a whole may appear hunchback lying on the waist, the overall center of gravity forward, most of the training members of the feedback for the anterior side of the knee pain, at the same time it is also found that in the only loosening of the waist does not drop the hips of the erroneous movement appeared, the trainer will appear to be the body slightly tilted backward, the knees are forward significantly more than the toes, but also appear the anterior side of the knee pain phenomenon, in line with the data describing in the literature of the dull pain. Movement is defined as all changes in physical activity that occur during movement. It includes movements, postures, shifts in position, and changes in form and condition of all parts of the body. In Taijiquan training, movement can refer to the execution of specific actions. In terms of boxing theory, the movement of Taijiquan is the transformation of yin and yang, and the change of reality and emptiness. Seeking constancy from change is the requirement for the process of movement; what changes is the physical form, but what remains unchanging is the requirement for the execution of the movement. In practice, it is more difficult to maintain the correctness of the movement in the change, which is not only a test of the body control but also a test of the body's loading bearing. Boxing theory says that "its root is in the feet, starting in legs", "section through", and " if there something is wrong, the body will be scattered, the disease should be sought by the waist and legs", indicating that the errors in the movement, most of them are related to the legs, which means that there is an interconnection and interdependence between these requirements. Most of them are related to the legs, which means that there is an interrelated and interdependent relationship between these requirements. therefore, It is important to ensure that each requirement is correct during the practice of taijiquan to ensure the fluidity and effectiveness of the movement as a whole. Negligence or deviation in any one part of the process may have an adverse effect on the whole and lead to the occurrence of knee injuries. In the training of Taijiquan, the foundation of "movement" is the winding work, combined with "its root is in the foot, starting in legs", which means that the force is generated by the ground from the leg to stomp and turn so as to carry out the change of the real and virtual in order to carry out the next action, and in the process of stomping and turning, combined with the requirements of the above taijiquan on the fixed position, it is necessary to buckle the knee to the toe. In the process of stomping and transferring, the practitioners often ignore this precaution in the movement, and it is easy for the knee to swing inwardly or outwardly during the movement, making the knee unstable, and the stomps transferring at the same time as the swinging will form a rotational pressure on the knee joints. In traditional Chen-style Taijiquan, often the leg muscle load is larger, but the main function of the knee joint lies in the flexion and extension, which may lead to uneven stress on the knee joint pressure is too large to produce pain or even injury, and the knee pain producing in the movement often occurs on both sides of the knee joint. Conclusion: Most of the traditional Chen's taijiquan practitioners have knee pain, often because the technical movement is not standardized or the training process only focuses on a certain aspect, loss of sight of the other, but taijiquan is a kind of "When moving everything moves" of the movement system. 4 Conclusion: Most of the traditional Chen's taijiquan practitioners have knee pain, often because the technical movement is not standardized or the training process only focuses on a certain aspect, loss of sight of the other, but taijiquan is a kind of "a movement has no immobility" of the movement system. Chen-style Taijiquan has self-containing system since the beginning of its training, and the training is a process of transformation from rigidity to flexibility. In this process, not only do we need to learn the standardization of movements, but we should also understand the theory of boxing in order to correct our own errors, which also explains the characteristic of "oral teaching" in traditional martial arts. In the development of modern society with the continuous development of the network, many people follow the network video for self-study, but they can not judge their own movements right or wrong by themselves, nowadays perhaps they can take the use of the human body two-dimensional measurement chart against the boxing spectrum boxing theory for correction. From the viewpoint of the whole Chen's Taijiquan training process, the knee pain and injury caused by the training process can be found in the "Chen-style Taijiquan Illustrations" with the corresponding movement error, so the study and research of the "Chen-style Taijiquan Illustrations" are of great significance in solving the knee pain in the process of Taijiquan practice.